Screening and identification of potential predictive biomarkers for Down's syndrome from second trimester maternal serum. (February 2014) - Yao, Yuan; Jiang, Ying; Han, Mei; Xia, Yu; He, Yuchen; Wang, Yonghu; Luo, Yang; Zhang, Bo
<x xml:space="preserve">Abstract</x> Objective: In this study, we aimed to search for noninvasive predictive biomarkers for prenatal diagnosis of Down's syndrome (DS). Methods: Maternal serum samples from five DS-affected pregnant women and five DS-unaffected women were analyzed by 2D gel electrophoresis and MALDI-TOF mass spectrometry to screen for potential predictive biomarkers of DS. Then, differential levels of dGTPase, β2-glycoprotein I (β2-GPI), complement factor H-related protein 1 precursor (CFHR1) and kininogen 1 isoform 2 were further verified by western blotting tests in another independent group. Results: Statistical analysis results revealed 29 protein spots whose levels differed significantly in the DS-affected pregnancies group. Of these, the eight most differentially expressed in DP were identified successfully. Among these, levels of dGTPase, CFHR1 and kininogen 1 were elevated significantly, whereas β2-GPI was reduced in DP. Discussion: These preliminarily verified proteins might serve as potential predictive biomarkers for DS-affected pregnancies.